COGNITIVE AND LINGUISTIC FEATURES OF EVENTIVE REALIZATION THROUGH ASSERTIVE SPEECH ACTS IN ENGLISH AND UZBEK (International journal of artificial intelligence, 2026)
This article investigates the cognitive and linguistic features involved in the realization of eventive information through assertive speech acts in English and Uzbek discourse. By examining how speakers structure and convey events, the study highlights both cross-linguistic similarities and differences. The research employs comparative linguistic and cognitive analysis to explore the semantic, syntactic, and pragmatic dimensions of assertive acts. Findings indicate that cultural, grammatical, and cognitive factors significantly influence the expression of events in both languages, providing insights into effective cross-cultural communication.